Situation Description and Critical Technology Analysis of Public Emergency Call Service Based on Internet of Vehicle - Jie Li (Dianxin kexue)
The situation of public emergency call service in Europe, USA and Russia etc was described. And it made analysis for technology indexes, telecommunication technologies and vehicle electronic technologies involved in emergency call. Then the development tendency of next generation emergency call technologies was described and some advices for how to construct public emergency call in China were given.